2015
DOI: 10.3109/02699206.2015.1029594
|View full text |Cite
|
Sign up to set email alerts
|

Non-word repetition in 2-year-olds: Replication of an adapted paradigm and a useful methodological extension

Abstract: Accurate non-word repetition (NWR) has been largely attributed to phonological memory, although the task involves other processes including speech production, which may confound results in toddlers with developing speech production abilities. This study is based on Hoff, Core and Bridges' adapted NWR task, which includes a real-word repetition (RWR) condition. We tested 86 typically developing 2-year-olds and found relationships between NWR and both receptive and expressive vocabulary using a novel measure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A variety of linguistic and experiential factors impact NWR accuracy, including stimulus length (Gathercole et al, 1991), phonological complexity (Szewczyk et al, 2018), and phonotactic probability/wordlikeness (Gathercole et al, 1991;Edwards et al, 2004;Szewczyk et al, 2018). Participants' vocabulary size (Gathercole and Baddeley, 1989;Munson et al, 2005;Hoff et al, 2008) and real-word repetition accuracy (Torrington Eaton et al, 2015) also predict NWR performance. Thus, although NWR was originally assumed to be a language-neutral diagnostic measure of phonological working memory, relevant experiential predictors, such as phonotactic probability, demonstrate that biologically-endowed working memory and experience with language, together, predict performance on the task (Gathercole and Baddeley, 1989;MacDonald and Christiansen, 2002).…”
Section: Nonword Repetition: An Important Indicator Of Speech-language Developmentmentioning
confidence: 99%
“…A variety of linguistic and experiential factors impact NWR accuracy, including stimulus length (Gathercole et al, 1991), phonological complexity (Szewczyk et al, 2018), and phonotactic probability/wordlikeness (Gathercole et al, 1991;Edwards et al, 2004;Szewczyk et al, 2018). Participants' vocabulary size (Gathercole and Baddeley, 1989;Munson et al, 2005;Hoff et al, 2008) and real-word repetition accuracy (Torrington Eaton et al, 2015) also predict NWR performance. Thus, although NWR was originally assumed to be a language-neutral diagnostic measure of phonological working memory, relevant experiential predictors, such as phonotactic probability, demonstrate that biologically-endowed working memory and experience with language, together, predict performance on the task (Gathercole and Baddeley, 1989;MacDonald and Christiansen, 2002).…”
Section: Nonword Repetition: An Important Indicator Of Speech-language Developmentmentioning
confidence: 99%
“…Earlier studies have shown that nonresponses to NWR items or drop-outs sometimes occur with 2-year-old children, especially as items get more difficult [8,13,26]. All children included in the study attempted NWR items; as stated earlier, 4 children refused and were not included in the study.…”
Section: Resultsmentioning
confidence: 99%
“…The tasks selected were meant to limit articulatory constraints, and the scoring approach attempted to account for articulation confounds related to normal phonological processes. Recent research has shown that using an individualized scoring method that controls for speech production errors for each child may be a better measure of NWR performance than globally applied approaches that assign credit for all possible normal phonological patterns [26]. Future studies with young children should consider each child's individual speech production inventory and patterns when scoring NWR items.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of linguistic and experiential factors impact NWR accuracy, including stimulus length (Gathercole et al, 1991), phonological complexity (Szewczyk, Marecka, Chiat, & Wodniecka, 2018), and phonotactic probability/wordlikeness (Edwards et al, 2004;Gathercole et al, 1991;Szewczyk et al, 2018). Participants' vocabulary size (Gathercole & Baddeley, 1989;Hoff, Core, & Bridges, 2008;Munson, Edwards, & Beckman, 2005) and real-word repetition accuracy (Torrington Eaton, Newman, Bernstein Ratner, & Rowe, 2015) also predict NWR performance.…”
Section: Nonword Repetition: An Important Indicator Of Speech-language Developmentmentioning
confidence: 99%
“…The gender distribution for the final sample of 84 participants was n=49 female and n=35 male children (see An additional n=39 children participated in the research program but either could not complete the NWR task or scored below the 10th percentile on the MCDI at 24 months; the data from these caregiver-child dyads are not analyzed here. See Torrington Eaton et al (2015) for further details on participant exclusion.…”
Section: Participantsmentioning
confidence: 99%